A cubic, how depressing

Algebra Level 2

The cubic polynomial

x 3 9 x 2 + 20 x + 2 x^3-9x^2+20x+2

can be expressed in terms of y y as

y 3 + c y + d , y^3+cy+d,

where c c and d d are real numbers and y y has a linear relationship with x . x.

What is the value of c + d ? c+d?


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Andy Hayes
Jan 20, 2017

Relevant wiki: Cardano's Method

Assuming you don't know the identity that depresses the cubic , let x = y p . x=y-p. Then the cubic is:

x 3 9 x 2 + 20 x + 2 ( y p ) 3 9 ( y p ) 2 + 20 ( y p ) + 2 y 3 3 p y 2 + 3 p 2 y p 3 9 ( y 2 2 p y + p 2 ) + 20 y 20 p + 2 y 3 + ( 3 p 9 ) y 2 + ( 3 p 2 + 18 p + 20 ) y + ( p 3 9 p 2 20 p + 2 ) . \begin{array}{l} x^3-9x^2+20x+2 \\ (y-p)^3-9(y-p)^2+20(y-p)+2 \\ y^3-3py^2+3p^2y-p^3-9(y^2-2py+p^2)+20y-20p+2 \\ y^3+(-3p-9)y^2+(3p^2+18p+20)y+(-p^3-9p^2-20p+2) . \end{array}

The 2nd degree term should have a 0 coefficient to fit the required form. Thus,

3 p 9 = 0 p = 3. \begin{aligned} -3p-9 &= 0 \\ p&=-3. \\ \end{aligned}

Substituting this value of p p back into the expression gives:

y 3 7 y + 8. y^3-7y+8.

Thus, c + d = 1 . c+d=\boxed{1}.

Here I propose a very simple solution Consider the cubic function: f ( x ) = x 3 9 x 2 + 20 x + 2 f(x) = x^3 - 9x^2 +20x +2

Now, transforming the cubic function to the depressed form is by substituting x = y b / 3 a x = y - b/3a

which in this case evaluates to x = y ( 9 ) / 3 ( 1 ) = y + 3 x = y - (-9)/3(1) = y+3

Hence,

f ( y + 3 ) = y 3 + c y + d f(y+3) = y^3 +cy + d

Sub y = 1 y = 1

f ( 4 ) = 1 + c + d f(4) = 1 + c + d

Evaluating f ( 4 ) f(4) gets 2 2

So

c + d = 2 1 = 1 c+d = 2-1 = 1

Surprised you didn't get any upvotes. Good job

Echizen Ryoma - 1 year, 7 months ago
Atul Kumar Ashish
Jan 20, 2017

We can write the equation as,
x 3 9 x 2 + 20 x + 2 = 0 x^3-9x^2+20x+2=0 .
x 3 9 x 2 + 27 x 27 27 x + 27 + 20 x + 2 = 0 x^3-9x^2+27x-27-27x+27+20x+2=0 .
( x 3 ) 3 7 x + 29 = 0 (x-3)^3-7x+29=0 .
( x 3 ) 3 7 x + 21 + 8 = 0 (x-3)^3-7x+21+8=0 .
( x 3 ) 3 7 ( x 3 ) + 8 = 0 (x-3)^3-7(x-3)+8=0 .
Comparing this equation with y 3 + c y + d = 0 y^3+cy+d=0 we get,
c = 7 c=-7 , d = 8 d=8 and the linear relation as y = x 3 y=x-3 .
Therefore, c + d = 7 + 8 = 1 c+d=-7+8=1 .




Nikola Djuric
Mar 2, 2017

put /$ x=y+9/3 /$ /newline $ (y+3)^3-9(y+3)^2+20(y+3)+2= $ /newline $ y^3+9y^2+27y+27-9y^2-54y-81+20y+60+2= $ /newline $ y^3-7y+8 $

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...